2016
DOI: 10.21083/partnership.v10i2.3449
|View full text |Cite
|
Sign up to set email alerts
|

Like, Comment, Retweet: Understanding Student Social Media Preferences

Abstract: The majority of academic libraries currently use one or more social media websites in their efforts to communicate and engage with students. Some of the most widely used sites are Facebook, Twitter, YouTube and Instagram. Education Library users at the University of British Columbia were surveyed and asked to rank whether they preferred receiving Education Library communications from Facebook, Twitter or WordPress (blogs). The results indicate that students ranked Facebook first, WordPress second and Twitter t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…The revelation was reflective of the study by Chu and Du (2013), which found out that 71.1 per cent of librarians in the UK were knowledgeable and used social media, whereas 13.1 per cent planned to use it later. The result is also in consonance with that of Win et al (2015), which indicated that 77 per cent of Canadian librarians believe that librarians should not only have knowledge in social media but also deepen their knowledge with time. Librarians were, however, limited in their application of the array of platforms available because majority were fond of mostly Facebook and Twitter.…”
Section: Discussionsupporting
confidence: 77%
“…The revelation was reflective of the study by Chu and Du (2013), which found out that 71.1 per cent of librarians in the UK were knowledgeable and used social media, whereas 13.1 per cent planned to use it later. The result is also in consonance with that of Win et al (2015), which indicated that 77 per cent of Canadian librarians believe that librarians should not only have knowledge in social media but also deepen their knowledge with time. Librarians were, however, limited in their application of the array of platforms available because majority were fond of mostly Facebook and Twitter.…”
Section: Discussionsupporting
confidence: 77%
“…Social media is a practical, low-cost method by which libraries can disseminate information as well as foster community engagement. Previous studies surrounding the use of social media in libraries have explored various aspects such as content (Shiri & Rathi 2013;Anderson 2015;Mon & Lee 2015;Joo et al 2018;Xie & Stevenson 2019;Joo et al 2020), stakeholder perceptions (Abidin et al 2013;Anwyll et al Winter 2013;Winn et al 2015;Cavanagh 2016;Shafawi & Hassan 2018;AlAwadhi & Al-Daihani 2019;Jones & Harvey 2019;Budu et al 2020;Pashootanizadeh & Rafie 2020;Williams et al 2021), and effective use strategies (Anwyll et al Fall 2013;Harmon & Messina 2013;Ramsey & Vecchione 2014;Smeaton & Davis 2014;Stone 2014;Valenza et al 2014;Mon 2015;Zou et al 2015;Peacemaker et al 2016;Rossmann & Young 2016;Bickford 2017;Gow 2017;Guevara 2018;Woodworth 2018;Fonseca 2019;Trucks 2019;Chaputula et al 2020). However, the majority of this literature has limited its focus to social media in the general sense or to individual platforms; thus, very little has been done to investigate and compare libraries' use of multiple platforms, particularly in-depth.…”
Section: Social Media Usage In Librariesmentioning
confidence: 99%
“…While an early study found that students felt hesitant about communicating with library staff on Facebook (Chu & Meulemans, 2008), a more recent study found that students ranked Facebook as their preferred social media platform for communications from the library (Winn, Groenendyk, & Rivosecchi, 2015). This is indicative of how Facebook has become a default platform for everyday communication.…”
Section: Literature Reviewmentioning
confidence: 99%